Child Diet and Maternal Responsiveness Mediate Effects of a Responsive Stimulation and Nutrition Intervention on Child Growth and Development: Evidence from Rural Pakistan. (29th May 2020) - Bliznashka, Lilia; McCoy, Dana; Siyal, Saima; Sudfeld, Christopher; Fawzi, Wafaie; Yousafzai, Aisha
Abstract: Objectives: To test the hypothesis that child diet and maternal responsiveness mediated the effects of an integrated responsive stimulation (RS) and enhanced nutrition (EN) intervention on child growth and development. Methods: We used data from the Pakistan Early Child Development Scale-up (PEDS) cluster-randomized controlled trial which evaluated the effectiveness of the Lady Health Worker (LHW) Program in rural Pakistan from 2010–2012. LHWs were randomized into one of four intervention arms (20 LHWs each): (1) RS: UNICEF-WHO Care for Child Development package (locally adapted), (2) EN: EN education and multiple micronutrient powders for children 6–24 mo, (3) RS + EN, and (4) Control. LHWs delivered the interventions in routine monthly home visits and group sessions. Mother-child pairs were enrolled form birth to 24 mo ( N = 1324). Primary outcomes were child growth (assessed with length-for-age Z-score (LAZ)) and development (assessed with the Bayley Scales of Infant and Toddler Development, Third Edition) at 12 and 24 mo. We examined whether child diet (assessed with the WHO indicator for minimum acceptable diet) and maternal responsiveness (assessed with the Observation of Mother-Child Interaction tool) at 12 mo mediated intervention effects at 24 mo. Structural equation modelling was used to estimate the total, direct and indirect (via child diet and maternal responsiveness) intervention effects on child growth and development at 24 mo. Results: The RS, EN and RS + EN interventions improved cognitive, language and motor development at 24 mo, but had no significant effect on LAZ and socio-emotional development. Child diet and maternal responsiveness mediated intervention effects on cognitive development, whereas maternal responsiveness alone mediated intervention effects on language and motor development. Despite the lack of significant total intervention effects on LAZ and socio-emotional development, there were significant positive indirect effects on LAZ via maternal responsiveness and child diet, and on socio-emotional development via maternal responsiveness. Conclusions: Child diet and maternal responsiveness are two important mechanisms which mediated the effect of a RS and EN intervention on child growth and development. Leveraging these mechanisms can help enhance the effectiveness of RS and EN interventions. Funding Sources: None.